2014
DOI: 10.1007/s11814-014-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic wet peroxide oxidation of phenol over Ce-Zr-modified clays: Effect of the pillaring method

Abstract: Preparation, characterization and catalytic activity of Zr-and Ce-Zr pillared clays with different method (direct, indirect, and under reflux), starting from Tunisian interstratified illite-smectite bentonite, are described. Zirconium pillared clays (Zr-PILC) revealed weaker thermal stability. To overcome this drawback, the addition of cerium (Ce) as the second metal component to Zr-PILC was attempted. Wet peroxide oxidation of phenol from industrial wastewaters was carried out over these catalysts. The cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The acidity and basicity of a catalyst play an important role in the decomposition of H 2 O 2 and in the CWPO of pollutants, as observed in previous works related to the CWPO of phenol compounds with carbon-based catalysts [44]. In works related to the CWPO with clay-based catalysts, a correlation between the acidity of the catalysts and their performance in the oxidation process has also been observed [22][23][24]. However, the cited previous studies used a qualitative methodology, based on FTIR analysis of base compound-saturated clays, and acidity and basicity were not quantified.…”
Section: Acid-base Characterizationmentioning
confidence: 55%
See 1 more Smart Citation
“…The acidity and basicity of a catalyst play an important role in the decomposition of H 2 O 2 and in the CWPO of pollutants, as observed in previous works related to the CWPO of phenol compounds with carbon-based catalysts [44]. In works related to the CWPO with clay-based catalysts, a correlation between the acidity of the catalysts and their performance in the oxidation process has also been observed [22][23][24]. However, the cited previous studies used a qualitative methodology, based on FTIR analysis of base compound-saturated clays, and acidity and basicity were not quantified.…”
Section: Acid-base Characterizationmentioning
confidence: 55%
“…Although this technology represent an interesting alternative, it has been scarcely studied so far for micropollutants abatement [18,20]. Clays play a prominent role as a catalyst in the field of organic pollutants removal by CWPO [21][22][23][24][25]. In this regard, natural clays can be chemically modified to increase their performance by different methods, such as activation or pillarization.…”
Section: Introductionmentioning
confidence: 99%
“…The ceria-based oxides take on potent oxygen storage property, and have dual roles of stabilizing the crystal structure and blocking the volume shrinkage. 20 The cerium oxide can be formed with the transition metal oxide to increase the dispersion and mechanical strength of active components on the catalyst surface at high temperature. Therefore, the loss of transition metal components can be inhibited, which makes catalyst more stable.…”
Section: Introductionmentioning
confidence: 99%
“…phenols undergo mineralization. CWPO over heteregeneous catalysts has been previously studied using transition metals and their complexes such as Fe, Cu and Mn and other metals such as Si, Al and Ti based catalysts [16][17][18][19][20][21][22][23]. In these studies, metals have been typically used either in their pure oxide forms or their oxide forms on a micro/mesoporous support such as ZSM-5, Y5, SBA-15, pillared clay or activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum-copper-iron, zirconium-cerium, manganese-copper on aluminum and ironaluminum containing PILC structures employed in the phenol oxidation exhibited good activity [16][17][18][31][32][33][34][35][36][37][38][39]. A limited number of studies involving titanium pillared structures have been reported in the literature [10,40].…”
Section: Introductionmentioning
confidence: 99%